IMPLEMENTASI DIGITAL SIGNATURE PADA ARSIP DI DINAS KEARSIPAN PROVINSI SUMATERA SELATAN - Arpa Pauziah; M. Izman Herdiansyah (Jusikom : Jurnal Sistem Komputer Musirawas, 2022)
Currently digital signatures or can also be called digital signatures are increasingly being used, especially for an archive. Digital archival technology is considered as different from traditional archives which refers to the preservation of physical objects such as Photo, Film and Cartography that can carry information. The importance of the right level of security in maintaining the authenticity of the archive requires strong evidence in the form of a digital signature that can be accessed via an Android Smartphone, then the document will be given a digital signature in the form of a hybrid Cryptosystem used for encryption and message description. using the RSA (Rivest Shamir Adleman) algorithm and the AES (Advanced Encryption Standard) algorithm. The reason for using the Hybrid Cryptosystem technique is to make it more secure and efficient.